PREVENTIVE EFFORTS AGAINST KONJO LANGUAGE EXTINCTION THROUGH MULTILINGUAL LEARNING - Saiful Saiful; Eny Syatriana; Firman Firman (Universitas Muhammadiyah Makassar, 2020)
The objectives of this study are: 1) to explore strategies for teaching Indonesian and English to integrate local languages, 2) to identify the factors that support the revitalization of local languages in multilingual learning, 3) to determine the perceptions of teachers and students towards the use of local languages in language learning.The results showed that Indonesian language learning at SMP Satap Kajang was carried out in accordance with the applicable curriculum, namely the K-13 curriculum. Meanwhile, learning English has been taught to students since grade I. Local languages have never been taught to students because there is no direction or order from the Bulukumba district education office about what local languages to teach, who teaches them, and how to learn local languages.The observation also found that SMP 1 Satap Kajang had the opportunity to carry out learning the Konjo language. This is supported by the existence of several native teachers who master the Konjo language (one science teacher, social studies, Indonesian, mathematics, religious education, and one English teacher) the teacher also welcomes if multilingual integrated learning is carried out besides the majority of junior high school students. is a native of Kajang who in fact speaks Konjo in general, although most 92% of students know Konjo language. This potential needs to be utilized for learning local languages, especially Konjo language, as an introduction to regional languages and prevent extinction.